IMPLEMENTASI METODE BIL QALAM DALAM MENINGKATKAN PEMBELAJARAN AL-QUR’AN - Fitrah Dwi Rahmawati; Noor Amirudin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
Al-Qur'an is Allah's word in the form of revelations conveyed to the Prophet Muhammad by the angel Gabriel, and contains Islamic teachings that were developed as guidelines for human life. The Qur'an is very important to learn and practice, so that it can be recited through reading and writing in studying it. For this reason, researchers want to explore further related to the implementation of the bil qalam method in improving the learning of the Qur'an for SD NU 1 Trate Gresik students, to the level of ability to read the Koran well and the supporting and inhibiting factors of its application. This type of research is qualitative, through primary and secondary data sources as well as data collection techniques through observation, interviews and documentation. Data analysis includes reduction, display data, and conclusion drawing/verification, by testing the validity of the data through source triangulation, technical triangulation and time transulation. The results showed that the implementation of the bil qalam method in improving the learning of the Koran at SD NU 1 Trate Gresik was carried out in four stages, namely 1) opening for 5 minutes, 2) talqin and ittiba' activities for 10 minutes, 3) 'urdhoh for 20 minutes, and 4) 'urdhoh or drill individually for 25 minutes.